Application of Universal Jurisdiction Principles to Cross-Country Money Laundering - Simanjutak, Efendi Lod; Kostruba, Anatoliy (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The fight against transnational crimes, particularly involving cross-border money laundering, requires a shift from a territorial to a universal jurisdiction approach. The aim of this investigation was to explore the practicality of universal jurisdiction principles in combating cross-border money laundering, which eludes effective criminal law mechanisms to arrest and prosecute offenders. Findings revealed that the crime of cross-border money laundering has not been considered one of the delicta juris gentium or international crimes, leading to an increase in the number of perpetrators who enjoyed refuge in various countries. Therefore, a universal jurisdiction approach is necessary to ensure that criminals are not immune to prosecution, and justice is served universally. As a result, every state must fulfill its obligation of arresting and prosecuting offenders wherever they may be found to uphold the law and universal justice. In conclusion, the need for a universal jurisdiction approach is crucial to combat the increasing threat of transnational crimes, particularly in the context of cross-border money laundering.